ABHD5 blunts the sensitivity of colorectal cancer to fluorouracil via promoting autophagic uracil yield - Ou, Juanjuan (Nat Commun, 2019)
The efficacy of Fluorouracil (FU) in the treatment of colorectal cancer (CRC) is greatly limited by drug resistance. Autophagy has been implicated in chemoresistance, but the role of selective autophagic degradation in regulating chemoresistance remains unknown. In this study, we revealed a critical role of ABHD5 in charging CRC sensitivity to FU via regulating autophagic uracil yield. We demonstrated that ABHD5 localizes to lysosome and interacts with PDIA5 to prevent PDIA5 from interacting with RNASET2 and inactivating RNASET2. ABHD5 deficiency releases PDIA5 to directly interact with RNASET2 and leave RNASET2 in an inactivate state, which impairs RNASET2-mediated autophagic uracil yield and promotes CRC cells to uptake FU as an exogenous uracil, thus increasing their sensitivity to FU. Our findings for the first time reveal a novel role of ABHD5 in regulating lysosome function, highlighting the significance of ABHD5 as a compelling biomarker predicting the sensitivity of CRCs to FU-based chemotherapy.